POLITENESS STRATEGIES USED BY THE CHARACTERS IN FROZEN II MOVIE - Pertiwi, Ni Putu Dika Yuni (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTCommunication is important for people in daily life. To start a good communication,people should know severals ways to make a good conversation with each other.However, there are some difficulties in applying the polite language to do acommunication. Based on those phenomena, this study of politeness strategies wasconducted. This study was conducted using the movie script of Frozen II movie to analyzethe utterances of the characters, in order to find out the types of politeness strategy usedby the characters. The data were classified using the theory of politeness by Brown andLevinson (1987). The result showed that the characters in Frozen II movie appliedPositive politeness, Off Record, Bald-on record, and Negative politeness.Keyword : Politeness strategies, Frozen II, MovieABSTRAKKomunikasi merupakan hal yang sangat penting dalam kehidupan sehari-hari. Untukmemulai komunikasi yang baik, seseorang hendaknya mengetahui beberapa cara untukmemulai komunikasi dengan manusia lainnya. Namun, ada kesulitan dalam menerapkanbahasa yang sopan saat memulai komunikasi. Berdasarkan fenomena tersebut, penelitiantentang strategi kesopanan ini dilakukan. Penelitian ini dilakukan menggunakantranskrip film Frozen II untuk menganalisa percakapan masing-masing karakter, untukmenemukan tipe strategi kesopanan yang digunakan oleh masing-masing karakter. Datadikumpulkan berdasarkan teori kesopanan yang dicetuskan oleh Brown and Levinson(1987). Hasilnya memperlihatkan bahwa karakter pada film Frozen II menggunakankesantunan positif, strategi tidak langsung, tanpa strategi, dan kesantunan negatif.Kata kunci: Strategi kesantunan, Frozen II, Film